CLASSIFICATION OF MOBILE GAMES IN THEORETICAL AND PRACTICAL TRAINING OF PHYSICAL EDUCATION TEACHERS - Семенов, Андрій (SWorldJournal, 2023)
We defined rivalry as a main criterion for classifying mobile games. Rivalry in mobile games manifests itself in the interaction of an individual and a team, which can manifest itself in the following ways: individual rivalry; collective rivalry; an indi